What is urea-triazone nitrogen? - Guodong Liu; Jeffrey Williamson (EDIS)
Foliar application of nitrogen and other nutrients essential for plant growth and development is an important practice for crop production. Most foliar nutrient N products contained the traditional N sources such as ammonium, nitrate and/or urea before urea-triazone N was available on the market. The traditional N sources have a greater salt index and leaf-burn potential than urea-triazone N. To avoid or minimize leaf burning, urea-triazone N fertilizers can be used instead of the traditional N sources. But growers have concerns about the safety of using triazone N fertilizers for commercial crop production because the fertilizers are still new to them. This 2-page fact sheet provides basic information on urea-triazone-based fertilizer for county faculty, crop consultants and advisors, growers, and students interested in commercial crop production. Written by Guodong Liu and Jeffrey Williamson, and published by the UF Department of Horticultural Sciences, October 2013. http://edis.ifas.ufl.edu/hs1233